Cutaneous side effects caused by treatment for inflammatory bowel disease - Dino Tarabar; Kandolf-Sekulović Lidija; Tatomirović Željka; Mijušković Željko; Milenković Zoran; Tarabar Olivera; Pecelj-Broćić Tanja (Vojnosanitetski Pregled)
nema